0027 Strengthening disaster injury epidemiology capacity: update on potential responses to various disasters. (26th April 2015) - Zane, David; VanderWerf-Hourigan, Lisa; Brown, Sheryll; Proescholdbell, Scott
Abstract : Statement of purpose: Every state and territory in the United States have communities that are at risk from natural disasters. It takes all of us to protect our communities from disasters and public health emergencies. Injury epidemiologists are an integral part of preparedness, response and recovery to disasters. However, to establish and maintain expertise in disaster epidemiology, there is a need for the development of a practical guide that illustrates potential injury epidemiological responses to various disasters. Methods/Approach: A disaster epidemiology special interest group within Safe States Alliance was formed to focus on injury epidemiology issues related to disasters. Through conference calls, this group focused on developing a guide of potential injury epidemiological responses to a variety of disasters. Results: A guide of potential injury epidemiological responses to six types of disasters (hurricane, flood, tornado, extreme heat, wildfire, and winter storms) was developed. The guide identifies potential injury epidemiological activities that might be conducted before, during, and after these disasters, and provides an injury epidemiology context within the disaster management cycle. The potential activities include identifying or enhancing current surveillance systems to monitor injuries among populations, using standardise injury data collection forms, mobilising/training staff and volunteers to assist in data collection efforts, preparing public health messages aimed at reducing injury morbidity and mortality, and preparing and disseminating injury-specific reports. Conclusions: Injury epidemiologists at the local, state, national, and territorial levels are an integral part of preparedness, response and recovery to disasters; to strengthen their capacity, a practical guide has been developed that illustrates potential injury epidemiological responses to various disasters. Significance and contribution to the field: Intended to be used in a planning context and to facilitate discussions with public health preparedness colleagues and other partners, this guide provides a significant advancement for the further development of injury epidemiology tools and approaches in other disaster settings.